Gastric cancer: from biomarkers to functional precision medicine - Albrecht, Philipp; Karabati, Ekin; Ebert, Matthias; Betge, Johannes (Trends in molecular medicine, 2025)
Gastric cancer (GC) remains a deadly disease because of late detection and limited treatment options at advanced stages. Treatment of patients with metastatic disease is based on chemotherapy, complemented by antibodies targeting HER2, VEGFR2, and more recently PD-1 or claudin 18.2. Further targets, such as FGFR2b, as well as novel drug classes including antibody-drug conjugates (ADCs) and bispecific antibodies, are promising developments in GC treatment. Despite the failure of several targeted agents, the landscape of GC therapy is evolving rapidly, facilitated by umbrella or platform precision medicine trials. The integration of next-generation sequencing and other omics techniques into molecular tumor boards, as well as functional drug testing on patient-derived models, might bring us closer to personalized oncology and ultimately improve patient survival.
Online verfügbar: 23. Juni 2025, Artikelversion: 3. Dezember 2025
Gesehen am 15.01.2026